1997
DOI: 10.1002/fedr.19971080714
|View full text |Cite
|
Sign up to set email alerts
|

Vegetationsökologische Untersuchungen auf nährstoffreichen Feuchtgrünland‐Brachen Sukzessionsverlauf und dynamisches Verhalten von Einzelarten

Abstract: ZusammenfassungBis weit in unser Jahrhundert bestanden grok Teile des Griinlandes des nordwestdeutschen Tieflandes aus extensiv bewirtschafteten artenreichen Feuchtwiesen. Eine Nutzungsaufgabe fuhrt in diesen Systemen zu Verschiebungen im Konkurrenzgefuge der Ptlanzenarten und lost Veriinderungen in der Vegetationszusammensetzung und -struktur aus. Die Sukzession nach der Nutzungsaufgabe ist durch die Abfolge charakteristischer Brachestadien gekennzeichnet: Nach einer Initialphase (Brachestadium I) kommt es zu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Billeter et al (2003) observed the opposite reaction of these two species in response to abandonment. They concluded that litter inhibits germination of C. davalliana, as suggested by several authors (Maas 1988;Bosshard et al 1988;Jensen 1997). However, not only litter removal, but also the increase in the proportion of flowering tillers of C. davalliana (Tab.…”
Section: Responses Of Carex Davalliana and Succisa Pratensismentioning
confidence: 73%
“…Billeter et al (2003) observed the opposite reaction of these two species in response to abandonment. They concluded that litter inhibits germination of C. davalliana, as suggested by several authors (Maas 1988;Bosshard et al 1988;Jensen 1997). However, not only litter removal, but also the increase in the proportion of flowering tillers of C. davalliana (Tab.…”
Section: Responses Of Carex Davalliana and Succisa Pratensismentioning
confidence: 73%